A new hybrid state estimation based on pseudo-voltage measurements - Chawasak Rakpenthai (2018)
© 2015 Institute of Electrical Engineers of Japan. Published by John Wiley & Sons, Inc. This paper presents a new hybrid state estimation method based on the concept of pseudo-voltage measurements for a power system containing both conventional and synchronizing phasor measurements. Actual measurement data is employed to calculate the magnitude and phase of the pseudo-voltage. In the proposed formulation, the measurement matrix describing the relations between the measured data and the state variables contains only 0 or 1. Then the state estimation problem is formulated based on the weighted least-squares criterion, and its solution can be obtained without using iterative procedures. Comparisons with previous hybrid state estimation methods have been performed on IEEE 14-bus, 57-bus, and 118-bus systems. Numerical experimental results indicate that the proposed approach yields solutions of comparable accuracy with other methods but with shorter computation times. Moreover, the proposed method also provides superior results in the presence of bad data.